AN ANALYSIS OF THE PERFORMANCE OF MERGERS AND ACQUISITIONS IN BOOM AND BUST PERIODS (CASESTUDY: UNITED KINGDOM) - Osagiede, Chukwuka Kingsley (2006)
Previous studies have confirmed significant positive returns to shareholders of target firm. Varied results have been reported for acquirers (positive, negative and zero returns). Several variables such as method of payment, type of acquisition (conglomerate and non-conglomerate mergers), managers' stake in the acquirers firm, have been used to explain the varied result to acquirers. Previous studies have examined the performance of acquirers over several years comprising both boom and burst periods. Similar studies carried out in different time periods have yielded contrasting results.